2018
DOI: 10.3390/f9040204
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Soil Methane Fluxes and Comparison between Two Forests in China

Abstract: Methane (CH 4) is a vital greenhouse gas with a 28-fold higher global warming potential than carbon dioxide when considering a molar basis for the time horizon of 100 years. Here, we investigated the variation of soil CH 4 fluxes, soil physiochemical properties, and CH 4-related bacteria community composition of two forests in China. We measured CH 4 fluxes using static chambers and analyzed soil bacterial communities using next-generation high-throughput sequencing in a temperate broad-leaved deciduous forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 84 publications
(110 reference statements)
1
4
0
Order By: Relevance
“…We also detected a clear seasonal dynamic of CH 4 in this study, with higher uptake rates in summer and lower rates in winter. The similar seasonal variations of net CH 4 fluxes have been reported in alpine grasslands (Guo et al, 2016;He et al, 2014;Pei et al, 2003;Wang et al, 2009), temperate grasslands (Chen et al, 2010;Du et al, 1997;Du et al, 2005;Liu et al, 2007;Wang et al, 1998;Wang et al, 2000;Wang et al, 2013), and forests ecosystem (Steinkamp et al, 2001;Wei et al, 2018). In our study site, net CH 4 uptake occurred during the nongrowing season with freezing soil surface and low soil temperature, consistent with observations in a shortgrass steppe in North American (Mosier et al, 1996), an alpine grassland in the Qinghai-Tibetan Plateau (Pei et al, 2003), and a typical semiarid steppe grassland in Inner Mongolia .…”
Section: Seasonal Dynamic and Its Controlssupporting
confidence: 75%
See 2 more Smart Citations
“…We also detected a clear seasonal dynamic of CH 4 in this study, with higher uptake rates in summer and lower rates in winter. The similar seasonal variations of net CH 4 fluxes have been reported in alpine grasslands (Guo et al, 2016;He et al, 2014;Pei et al, 2003;Wang et al, 2009), temperate grasslands (Chen et al, 2010;Du et al, 1997;Du et al, 2005;Liu et al, 2007;Wang et al, 1998;Wang et al, 2000;Wang et al, 2013), and forests ecosystem (Steinkamp et al, 2001;Wei et al, 2018). In our study site, net CH 4 uptake occurred during the nongrowing season with freezing soil surface and low soil temperature, consistent with observations in a shortgrass steppe in North American (Mosier et al, 1996), an alpine grassland in the Qinghai-Tibetan Plateau (Pei et al, 2003), and a typical semiarid steppe grassland in Inner Mongolia .…”
Section: Seasonal Dynamic and Its Controlssupporting
confidence: 75%
“…Contrasting to our observation, Wang et al () found, the alpine meadow was weak sink during the growing season but was neutral during the nongrowing season, probably due to higher altitude (4,600–4,800 m), deeper permafrost depth, thicker snow cover, and lower temperature during winter. No clear seasonal trend of the net methane uptake flux was found in a tropical rainforest in southern China due to its relatively high and stable soil temperature all year‐round (Wei et al, ). This study suggested that the net CH 4 flux is highly dynamic at both diurnal and seasonal scales, which are predominately determined by the temporal changes in climate factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a continental monsoon climate with four distinct seasons [ 64 ], with an average annual temperature of 15.1 °C, an average annual precipitation of approximately 900 mm, an average annual evaporation of 991.6 mm, and an average annual relative humidity of 68% [ 65 , 66 , 67 , 68 ]. The climate is between the northern subtropical and warm temperate zones [ 64 , 69 ]. The corresponding vegetation transitions from deciduous broadleaf forest to evergreen broad-leaved forest [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…Castaldi et al, 2020; Gatica et al, 2020; Liu et al, 2017; MacCarthy et al, 2018; Zhao et al, 2019). Moreover, studies that analysed the relationships of soil micro‐organisms with GHGs only focussed on microbial abundance and/or community dynamics (Drewer et al, 2021; Hamamoto et al, 2022; Monteiro et al, 2020; Wei et al, 2018). Therefore, we proposed a study to integrate soil physical and chemical attributes evaluations with soil microbiota activity in order to understand their relationships with GHGs fluxes, especially under native subtropical forests and pine plantations.…”
Section: Introductionmentioning
confidence: 99%